Utilization of Carboxymethyl Cellulose (CMC) from Coconut Coir Waste (Cocos nucifera) as a Stabilizer in Red Bean (Phaseolus vulgaris L) Vegetable Milk - Nasution, Rumondang Bulan; Simanungkalit, Roberto Carlos (Journal of Chemical Natural Resources, 2023)
Carboxymethyl cellulose (CMC) synthesis from coconut coir waste provides an alternative that can be used as a stabilizer to manufacture red bean milk. The first step is to isolate alpha-cellulose with a 2% NaOH solution. Second, the etherification process is alkalization with isopropanol and 17.5% NaOH solution to produce alkaline cellulose, and then the carboxymethylation process with sodium monochloride acetate (NaMCA) and characterized by FT-IR. The resulting carboxymethyl cellulose is purified by centrifugation. Red bean milk was analyzed using proximate analysis, viscosity, percent stability, pH, and organoleptic content by varying CMC 0.1, 0.2, and 0.5%. The alpha cellulose obtained was 13.37%, and the CMC produced from the etherification and purification process was 5.97 g. The characterization of alpha-cellulose showed (OH) at wave number 3441cm-1, and the CMC characterization showed carbonyl (COO-) at wave number 1604.77 cm-1 and group ether (CH2-O-CH2) at wave number 1419.77. Proximate analysis of red bean milk protein content of 2.75%, carbohydrates 10.27%, fiber 8.5%, and fat 18.57% and results based on viscosity and percent stability were obtained by adding 0.5% CMC and organoleptic test results adding CMC preferably with 0.3%, the texture is not too thick and even, and the aroma of red beans is typical.